2019
DOI: 10.1155/2019/9206951
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Astragalus membranaceus and Angelica sinensis Inhibits Lung Cancer and Cachexia through Its Immunomodulatory Function

Abstract: Lung cancer and its related cachexia are the leading cause of cancer death in the world. In this study, we report the inhibitory effect of the combined therapy of Astragalus membranaceus and Angelica sinensis, on tumor growth and cachexia in tumor-bearing mice. Lewis lung carcinoma cells were inoculated into male C57BL/6 and CAnN.Cg-Foxn1nu nude mice. After tumor inoculation, mice were fed orally by the combination of AM and AS in different doses. In C57BL/6 mice, the combination of AM and AS significantly inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Oncoviruses can enable different carcinogenesis stages, with one such virus being the HPV. Although within two years of infection most HPV infections can be cleared or deactivated, high risk HPV types remain and can progress to CC 26 . The DNA of high-risk HPV was found in 99.7% of CC specimen 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Oncoviruses can enable different carcinogenesis stages, with one such virus being the HPV. Although within two years of infection most HPV infections can be cleared or deactivated, high risk HPV types remain and can progress to CC 26 . The DNA of high-risk HPV was found in 99.7% of CC specimen 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the therapeutic approaches or agents for cancer cachexia are currently limited. Traditional Chinese Medicine is widely used in relieving cachexia symptoms (38,39). According to the theory of TCM, cancer cachexia belongs to a kind of consumptive disease, and the Yang-qi deficiency along with toxin stagnating is considered as its main pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This medicinal plant belongs to the Apiaceae family which many members of this family have found out to have anti-cancer effects. In other similar studies; Wu and colleagues stated that the extract of Angelica sinesis can inhibit the immunomodulatory function of lung cancer cell lines and down-regulate the expression of NFκΒ, STAT3, HIF-1α, and VEGF in tumors (Wu et al, 2019). In another project on members of the Apiaceae family, Goodarzi and researchers evaluated the pro-apoptotic effect of Cuminum cyminum on breast cancer cell line (MCF-7) and reported that it can be considered as a future chemotherapeutic drug and further studies has been suggested (Goodarzi et al, 2020).…”
Section: Introductionmentioning
confidence: 94%